How Do Children of Parents With Mental Illness Experience Stigma? A Systematic Mixed Studies Review - Dobener, Lisa-Marie; Fahrer, Julia; Purtscheller, Daniel; Bauer, Annette; Paul, Jean Lillian; Christiansen, Hanna (Frontiers in Psychiatry, 2022)
Stigma can have devastating health and wellbeing impacts, not just on people with mental health problems, but on people associated with the stigmatized person. This is called stigma-by-association. Children whose parents have mental health problems are a particularly vulnerable group, and stigma acts as a mechanism, contributing to the transgenerational transmission of mental disorders. The current study is a systematic mixed studies review, synthesizing knowledge about how this group of children experience stigma-by-association. Overall, 32 studies were included, after a systematic search including quantitative, qualitatative, and mixed methods studies. The methodological quality was assessed and qualitative content analysis undertaken. We grouped children’s stigma experiences into four dimensions, i.e. experienced stigma, anticipated stigma, internalized stigma, and structural discrimination. Results show that stigma is an important factor in those children’s lives, and needs further investigation in qualitative and quantitative research. The current study emphasizes the importance of anti-stigma interventions and campaigns.